1988
DOI: 10.1002/aoc.590020113
|View full text |Cite
|
Sign up to set email alerts
|

Methylation of inorganic lead by Tamar Estuary (UK) sediments

Abstract: Tetramethyllead (TML) has been produced from inorganic lead salts using biologically active sediments and waters from the Tamar Estuary, S.W. England. The TML production was a twostage process involving an initial lag phase of about 100 hours followed by the exponential appearance of TML, which amounted to about 0.03% of total added lead. The methylation process is discussed in the context of lead transport in estuaries

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…The biomethylation of Pb(II) has been reported to be catalysed by Pseudomonas sp. (Walton et al , 1988; Wong et al , 1975), Alcaligenes sp. (Wong et al , 1975), Acinetobacter sp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The biomethylation of Pb(II) has been reported to be catalysed by Pseudomonas sp. (Walton et al , 1988; Wong et al , 1975), Alcaligenes sp. (Wong et al , 1975), Acinetobacter sp.…”
Section: Introductionmentioning
confidence: 99%
“…(Wong et al , 1975) and Bacillus sp. (Walton et al , 1988). In general, two forms of volatile methylated lead have been identified as products of microbial activity: tetramethyl (Me 4 Pb) and trimethyl (Me 3 Pb) lead.…”
Section: Introductionmentioning
confidence: 99%
“…In concentrated solutions, 1 decomposed rapidly to a black insoluble material. Deprotection of 1 with sodium tetraborate (borax) in MeOH/THF, which is the mildest method for the deprotection of Me,Si-substituted alkynes [25], was rapid and quantitative, but decomposition of the formed parent C,,H4 chromophore 3 occurred immediately upon evaporation of solvent. Even in dilute solution, 3 decomposed rapidly and could, therefore, not be characterized.…”
mentioning
confidence: 99%
“…Moreover, Pb is not an essential nutrient in the metabolic processes of plants and/or animals, and it can accumulate to high levels and become toxic to organisms. [8][9][10] were capable of converting organic/ inorganic forms of Pb into less toxic derivatives. Several chemical methods have been developed to control the dispersion and biomagnication of metals from contaminated soil.…”
Section: Introductionmentioning
confidence: 99%
“…7 Several studies reported that the bacterial strains such as Pseudomonas sp., Bacillus sp., Acinetobacter sp., Flavobacterium sp., Aeromonas sp. [8][9][10] were capable of converting organic/ inorganic forms of Pb into less toxic derivatives. However, survival of the bacteria in the contaminated soil is essential for biotransformation of Pb since these reactions are enzyme mediated.…”
Section: Introductionmentioning
confidence: 99%